Comparison of marginal integrity of ceramic and composite veneer restorations luted with two different resin agents: an in vitro study - (:unkn) unknown (My University, 2002)
PURPOSE: The aim of the present study was to examine the marginal integrity of a composite veneer, Artglass, in comparison to a ceramic veneer, IPS Empress, by using two different luting agents. The study also aimed to evaluate the effect of grit blasting on marginal integrity of IPS Empress ceramic veneers. MATERIALS AND METHODS: A total of 42 human maxillary incisors were used to construct 14 veneers for each experimental group: (1) Artglass veneers, (2) IPS Empress veneers with grit blasting, and (3) IPS Empress veneers without grit blasting. Veneers were luted with Variolink II High Viscosity and Variolink Ultra. The restored teeth were sectioned buccolingually and mesiodistally, and marginal gap width measurements were made at 200x magnification. The data were statistically analyzed with analysis of variance. RESULTS: The mean marginal gap width varied from 105 to 182 microns. No significant differences were recorded between the marginal gap widths in relation to different types of veneers or luting agents. However, significantly higher marginal discrepancies were observed for the incisal margins of IPS Empress veneers without grit blasting. CONCLUSION: In view of the higher marginal discrepancy of IPS Empress veneers divested without grit blasting, the use of this alternative technique was not beneficial. The use of a highly filled resin luting agent (Variolink Ultra) did not cause an increase in marginal gap widths of the veneers.
Keywords: Humans; Analysis of Variance; Incisor; Dental Porcelain; Dental Veneers; Composite Resins; Statistics, Nonparametric; Dental Bonding; Aluminum Silicates; Glass Ionomer Cements; Resin Cements; Dental Marginal Adaptation; Silicate Cement